Estimating fugitive methane emissions from oil sands mining using extractive core samples. (November 2016) - Johnson, Matthew R.; Crosland, Brian M.; McEwen, James D.; Hager, Darcy B.; Armitage, Joshua R.; Karimi-Golpayegani, Mojgan; Picard, David J.
Abstract: Fugitive methane emissions from oil sands mining activities are a potentially important source of greenhouse gas emissions for which there are significant uncertainties and a lack of open data. This paper investigates the potential of a control-system approach to estimating fugitive methane emissions by analyzing releasable gas volumes in core samples extracted from undeveloped mine regions. Field experiments were performed by leveraging routine winter drilling activities that are a component of normal mine planning and development, and working in conjunction with an on-site drill crew using existing equipment. Core samples were extracted from two test holes, sealed at the surface, and transported for off-site lab analysis. Despite the challenges of the on-site sample collection and the limitations of the available drilling technology, notable quantities of residual methane (mean of 23.8 mgCH4 /kg-core-sample (+41%/−35%) or 779 mgCH4 /kg-bitumen (+69%/−34%) at 95% confidence) were measured in the collected core samples. If these factors are applied to the volumes of bitumen mined in Alberta in 2015, they imply fugitive methane emissions equivalent to 2.1 MtCO2 e (as correlated with bitumen content) or 1.4 MtCO2 e (as correlated with total mined material) evaluated on a 100-year time horizon. An additional ∼0.2 Mt of fugitive CO2 emissions could also be expected. Although additional measurements at a larger number of locations are warranted to determine whether these emissions should be considered as additive to, or inclusive of, current estimates based on flux chamber measurements at the mine face, these first-of-their-kind results demonstrate an intriguing alternate method for quantifying fugitive emissions from oil sands mining and extraction. Graphical abstract: Image 1 Highlights: Core samples were used to estimate fugitive CH4 emissions from oil sands mining. Residual methane released when samples heated to relevant process temperatures. New emission factors imply 2015 mined Alberta oil sands fugitive CH4  ≳ 1.4–2.1 MtCO2 e. Routine drilling operations could be leveraged to improve emissions estimates.